THE RESULTS OF VERIFICATION OF THE CORRECT EXECUTION OF THE SEQUENCE OF EXPERIMENTS ON THE MATHEMATICAL OPTIMIZATION OF THE PROCESS OF OBTAINING MELAMINE FORMALDEHYDE RESIN - N. V. Valiev (Web of Journals Publishing, 2024)
The degree of accuracy of experiments is important in studying the processes of synthesis of melamine formaldehyde resin. For this purpose, using the Maple computer program, the level of accuracy of the experiments was studied.
Keywords: chemical engineering, melamine, formaldehyde, mathematic planning, Box-Wilson, Maple.